MANGANESE PROSPECT IDENTIFICATION USING MAGNETIC AND INDUCED POLARIZATION METHODS - Taufan, Yoqi Ali; ilmi, irpan; Denis, Mutebi; Nur, Andi Agus; Syafri, Ildrem (Bulletin of Scientific Contribution, 2018)
Surveys have been carried out using Magnetic and Induced Polarization methods over area dominated by Bobonaro complex formation. This survey was conducted with the purpose to identify a mineral source using data of magnetic, conductivity and resistivity of rock. Data acquisition applied 5 m dipole space with 50 m maximal depth coverage.The interpretation was conducted by analyzing 2D and 3D sections of resistivity inversion, subsurface Induced Polarization, and geomagnetic anomaly. The interpretation result of chargeability anomaly indicates that mineral source occurred as a mineral of manganese with thin layer spreading in complex structural sediment.  As is shown from IP anomaly supported by magnetic data obtained, the anomaly has a spread of 3 m to 10 m depth from the surface. The trend of anomaly has a continuity at other locations where is predicted as the manganese mineralization source.